Extremism, free speech and counter-terrorism law and policy - Cram, Ian (Routledge studies in extremism and democracy, 2019)
"This edited collection addresses a number of free speech vs security concerns that are engaged by counter-terrorism law and policy makers across a number of liberal democracies, and explores the delicate balance between free speech and the censoring of views that promote hatred or clash with fundamental democratic values. It does this by looking at the perspectives and level of disagreement between those who consider today's counter-terrorism and extremism strategies to be a soft and liberal approach, and those who believe these strategies disproportionately impact freedom of expression and association and non-violent political dissent. The contributors include academics, practicing lawyers, and think-tank analysts who examine whether universities and schools incubators of violent radicalism and debate, and whether the views of 'extremist' speakers and hate preachers need to be censored. Outside the UK, critical discussion of the regulation of counter-terrorism, extremism, and free speech in other liberal democracies is also offered. This book will be of great interest to researchers and practitioners with interests in extremism, terrorism, civil rights, and freedom of speech."